B.1.617.2 variant and increasing surge of COVID-19 in Nepal - Shrestha, Umid Kumar (Nepal Mediciti Medical Journal, 2021)
As the coronavirus disease 2019 (COVID-19) pandemic goes on, there has been an evolution of severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) leading to the mutations. As of May 2021, the B.1.617 variant has become the dominant strain across India and has spread to about 40 nations. Among different strains of B.1.617, the mutations of great concern are E484Q, L452R, P681R and T478K, because of the stronger affinity of the spike protein of these mutants for the Angiotensin Converting Enzyme (ACE) 2 receptor making it more transmissible and infectious, and causing decreased recognition capability of the immune system. Among the sub-variants of B.1.617, the B.1.617.3 shares the L452R and E484Q mutations found in B.1.617.1, whereas B.1.617.2 does not have the mutation E484Q, but it has the T478K mutation, not found in B.1.617.1 and B.1.617.3. With the increasing surge of COVID-19 in India with dominant B.1.617.2 variant, Nepal also witnessed the parallel increasing number of COVID-19 cases starting from the early weeks of April 2021, which could have been triggered by the influx of people due to the long open border of Nepal with neighboring India. Obviously, as of May 2021, the second wave of COVID-19 in Nepal has been linked with this new variant B.1.617.2 of SARS-CoV-2. Despite the challenges imposed by the new variant, the vaccines are likely to remain effective against different variants including B.1.617.2 and to limit severe disease. Moreover, there is an urgent need of an effective locally based system for the testing, contact tracing, and isolation. The risk reduction behavior, such as washing hands frequently, keeping at least 1m distance from others and wearing a mask, should be adapted to the daily habits during this COVID-19 pandemic era. There should be a long term planning for the control of COVID-19 with the effective vaccination and public health measures; otherwise, even after the control of the current surge, the next wave of COVID-19 might be knocking at door in the coming days.